2014
DOI: 10.1111/1475-679x.12039
|View full text |Cite
|
Sign up to set email alerts
|

When the Use of Positive Language Backfires: The Joint Effect of Tone, Readability, and Investor Sophistication on Earnings Judgments

Abstract: Recent studies document that market participants react positively to the positive language sentiment or tone embedded in financial disclosures, and that investors' reactions to negative news are more muted with poor disclosure readability. However, while language sentiment and readability co-occur in practice, their joint effects remain largely unexplored. In an experiment with MBA students as participants, we investigate how the effect of language sentiment varies with readability and investor sophistication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
162
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(180 citation statements)
references
References 57 publications
10
162
3
5
Order By: Relevance
“…These results are different from the Tan et al [5] study, wherein they find that low readability obscures but does so with low-sophistication investors only, while high readability essentially establishes a baseline of both groups understanding the financial information. There may be several factors in play to explain this.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These results are different from the Tan et al [5] study, wherein they find that low readability obscures but does so with low-sophistication investors only, while high readability essentially establishes a baseline of both groups understanding the financial information. There may be several factors in play to explain this.…”
Section: Discussioncontrasting
confidence: 99%
“…There may be several factors in play to explain this. Firstly, the two studies examine different main effects, with Tan et al [5] focusing on the framing effect of positive tone as jointly moderated by investor sophistication and readability, while this study focuses on the main effect of readability on investors of differing …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Ghose and Ipeirotis (2011) show that higher readability of user-generated online reviews positively influences purchase decisions. Similarly, Tan et al (2014) found that readability moderates the effect between the presentation of financial reports and the investors' earning evaluations.…”
Section: Readability Of Ideasmentioning
confidence: 89%